(3GdTgH GddGeYI aj GdSjGSI GdfGaYIs - (3YHO Gddg Hf jhSa Hf QVhGf GdfLGQj GdeGdbj, CHh GdbGSe , J (B782 (3g`s ((3GdMSf Hf Ydi GdUbdi GdCfOdSi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi OHQ HMceJg GdHdjZI CehQ HYGOg CeG HYO aEfi LeYJ ef SjGSGJ Gdedhc WQa ef GdJGQjN s
(3BNQgG (B:s
(3ajSJTYQhG hGKbkG HGdfUQ YGedkG Ydi Cf KbJg HGdeXaQI hCf MRH Gddg Ye GdZGdHhf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs